Cellular and Molecular Biology for Human. - Guraya, S. S. (New Age International Pvt. Ltd., Publishers, 2007)
The basic and applied knowledge of cellular and molecular biology of human oogenesis, ovulation and early embryogenesis especially fundamentals, biomedical and clinical implications in relation to infant disorders for ensuring the formation of normal eggs or ova is essential. Keeping this in view, there is a great interest in the study of cellular and molecular biology of primordial follicles or oocytes and normal development, growth, differentiation and biochemistry of oogenesis i.e. oocyte growth, maturation, ovulation, fertilization of human ova in vivo and in vitro to develop better strate.